Issues of Gender & Sexuality in Special Needs Children: Keeping Students with Autism & Learning Disability Safe at School - Lawson, Wenn B. (Journal of Intellectual Disability - Diagnosis and Treatment, 2017)
The following paper addresses some of the issues presented by students with Special Needs, (especially autism) at school. It particularly focusses upon sexuality and gender. For example, autism and gender dysphoria appear to co-occur more often than in typically developing students. However, these young people may not understand how their reality translates to living within the public arena. This is also true of sexuality. Acceptance, understanding and accommodation of these students needs to inform our measures for keeping safe at school; this is of utmost priority.